Landscape quality and soil loss across the simulation of environmental scenarios in the Brazilian savannah - Santos Arruda de Lim, Gabriella a; Clementino Ferreira, Nilson; Ferreira, Manuel Eduardo (Sociedade & Natureza, 2020)
The present study used ecology fundamentals, through the application of some spatial metrics, to verify the current fragmentation of the landscape in the Metropolitan Region of Goiânia (RMG), with the objective of establishing priority areas for forest maintenance and recomposition. For this, three scenarios were simulated, the first current, the second considering the restoration of forests in areas of permanent protection (APP) along the water courses, while in the third scenario the reforestation in the regions of high and very high environmental vulnerability study area. This research also proposed to evaluate the loss of soil by laminar erosion applied to the three proposed scenarios for the region. It was found that in the RMG, according to the current configuration of the landscape, there has been high fragmentation of remnant vegetation, where the reforestation is highly recommended. The spatialization of these results and the indication of areas for reforestation and conservation serve as a guide to public policies and in collective decision-making involving all the municipalities of RMG.